2013
DOI: 10.3103/s1068364x13050049
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen storage in multilayer carbon nanotubes

Abstract: Multilayer carbon nanotubes obtained by pyrolysis and mechanical activation of plant derived amorphous carbon are excellent sorbents for hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It seems to that high pressure was essential to promote the diffusion of the targeted gas into the inner structure of conventional CNMs for most of the adsorption/storage processes 178 . However, Onishchenko et al reported that biomass-based CNTs derived from mechanical activation of rusty peat moss, katerina SV corn, priozernyi-4 cotton and thorny bamboo presented excellent H2 adsorption capability even at a low pressure (0.5 MPa) and at room temperature (24 ℃) [179][180][181] . It was found that the adsorption capacity of H2 were greatly affected by the type of feedstock, the mechanical activation time, the adsorption pressure and the adsorption temperature.…”
Section: Other Applicationsmentioning
confidence: 99%
“…It seems to that high pressure was essential to promote the diffusion of the targeted gas into the inner structure of conventional CNMs for most of the adsorption/storage processes 178 . However, Onishchenko et al reported that biomass-based CNTs derived from mechanical activation of rusty peat moss, katerina SV corn, priozernyi-4 cotton and thorny bamboo presented excellent H2 adsorption capability even at a low pressure (0.5 MPa) and at room temperature (24 ℃) [179][180][181] . It was found that the adsorption capacity of H2 were greatly affected by the type of feedstock, the mechanical activation time, the adsorption pressure and the adsorption temperature.…”
Section: Other Applicationsmentioning
confidence: 99%
“…The properties of multilayer carbon nanotubes cre ated by the mechanical activation of amorphous car bon that, in turn, had been obtained from brown sph agnum moss, corn waste, cotton, and spiny bamboo were considered in [3][4][5][6][7][8]. Treatment in a planetary mill for 1-27 h was used for mechanical activation of the amorphous carbon.…”
mentioning
confidence: 99%
“…The volume of the carbon nanotubes formed in the mechanical activation of amorphous carbon depends linearly on the time of mechanical activation (1-27 h) in the planetary mill [5].…”
mentioning
confidence: 99%